2015
DOI: 10.3109/09637486.2015.1093609
|View full text |Cite
|
Sign up to set email alerts
|

Milk and dairy consumption correlates with cerebral cortical as well as cerebral white matter volume in healthy young adults

Abstract: The objective of this study was to investigate the relation between habitual milk and dairy consumption and brain morphology as assessed by magnetic resonance imaging (MRI) investigations in 119 young healthy university students. MRI measurements were performed on a Siemens Magnetom Trio Tim (3T) system while FreeSurfer software suite was used for volumetric segmentation. Dietary habits related to milk and dairy consumption were assessed by a structured questionnaire. Total cerebral cortex, total cerebral whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Finally, it has recently been shown that among dairy products, cottage cheese and milk consumption were associated with higher total cerebral cortex volume (male, p = 0.005; and female, p = 0.025), and higher total cerebral white matter (men, p = 0.006) (Darnai et al , 2015). The author did not argue whether it was beneficial and offer as explanation that casein (main protein of cottage cheese) has a propensity to cross the blood brain barrier.…”
Section: Metabolic Response To Cottage Cheese Ingestionmentioning
confidence: 99%
“…Finally, it has recently been shown that among dairy products, cottage cheese and milk consumption were associated with higher total cerebral cortex volume (male, p = 0.005; and female, p = 0.025), and higher total cerebral white matter (men, p = 0.006) (Darnai et al , 2015). The author did not argue whether it was beneficial and offer as explanation that casein (main protein of cottage cheese) has a propensity to cross the blood brain barrier.…”
Section: Metabolic Response To Cottage Cheese Ingestionmentioning
confidence: 99%
“…It could be the reason why the high consumption of cakes attenuated the effect of energy drinks on brain function.We also found participants in NDG drank a large amount of milk. It has been reported that the volumes of the cerebral cortex and cerebral white matter are signi cantly correlated with milk and dairy consumption in healthy young adults(Darnai et al, 2015). It has also been reported that a well-balanced diet that includes milk and dairy products is effective in improving sleep quality(Komada et al, 2020).…”
mentioning
confidence: 99%